2011
DOI: 10.1080/15427951.2011.601233
|View full text |Cite
|
Sign up to set email alerts
|

Scaled Gromov Four-Point Condition for Network Graph Curvature Computation

Abstract: In this paper, we extend the concept of scaled Gromov hyperbolic graph, originally developed for the thin triangle condition (TTC), to the computationally simplified, but less intuitive, four-point condition (FPC). The original motivation was that for a large but finite network graph to enjoy some of the typical properties to be expected in negatively curved Riemannian manifolds, the delta measuring the thinness of a triangle scaled by its diameter must be below a certain threshold all across the graph. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…We use the notation D u 1 ,u 2 ,u 3 ,u 4 = max i, j∈{1,2,3,4} d u i ,u j to indicate the diameter of the subset of four nodes u 1 , u 2 , u 3 and u 4 . By using theoretical or empirical calculations, the authors in [42] provide the bounds shown in Table III.…”
Section: Checking Hyperbolicity Via the Scaled Hyperbolicity Approachmentioning
confidence: 99%
“…We use the notation D u 1 ,u 2 ,u 3 ,u 4 = max i, j∈{1,2,3,4} d u i ,u j to indicate the diameter of the subset of four nodes u 1 , u 2 , u 3 and u 4 . By using theoretical or empirical calculations, the authors in [42] provide the bounds shown in Table III.…”
Section: Checking Hyperbolicity Via the Scaled Hyperbolicity Approachmentioning
confidence: 99%
“…In this case, we return B G−C (p, (∆/3) − α ∆) = B G (p, (∆/3) − α ∆) as our solution. The size requirement follows since | B G (p, (∆/3) − α ∆) | < ζ n was shown in (22). Note that nodes in B G (p, (∆/3) − α ∆) can only be connected to nodes in C, and thus h G (B G (p, (∆/3) − α ∆) ) ≤ | C | / | B G (p, (∆/3) − α ∆) | ≤ (∆/3)d α∆ / n ε log d e/8 < n α−(ε log d e/8) log n < n 1/(7 ∆ 1/2 log(2d)) − (ε/(8 ln d) ) log n < ε where the penultimate inequality follows since ∆ = ω(1).…”
Section: Application To the Small Set Expansion Problemmentioning
confidence: 96%
“…There are many well-known measures of curvature of a continuous surface or other similar spaces (e.g., curvature of a manifold) that are widely used in many branches of physics and mathematics. It is possible to relate Gromov-hyperbolic curvature to such other curvature notions indirectly via its scaled version, e.g., see [45,46,56].…”
Section: Gromov-hyperbolic Curvaturementioning
confidence: 99%